Agronomic characteristics of pumpkin fruits of “Tetsukabuto”hybrid as a function of 2,4-D doses - de Miranda, Flávia Fernandes Ribeiro; do Nascimento, Ildon Rodrigues; Chaves, Prínscilla Pâmela Nunes; Muraishi, Cid Tacaoca; Dourado, Daisy Parente (Comunicata Scientiae, 2018)
Due to the short flowering period of the pumpkin hybrid ‘Tetsukabuto’, a poor pollination may influence the fruit production. In thissense, the objective of this study was to evaluate agronomic characteristics of the pumpkin hybrid (Tetsukabuto) as a function of 2,4-D doses as phytohormonal inducer. The experiment was conducted in the field, in a randomized block design with four replications and five plants per plot. It was established with eight treatments, seven of them increasing doses of 2,4-Dichlorophenoxyacetic acid (187.5, 200, 212.5, 225, 237.5, 250 and 262.5 mg L-1) and a control (flowers fertilized with pollen). At 110 days after sowing it was made a fruit harvest, evaluating the following characteristics: yield, fruit mean weight, texture of bark, fruit shape and cycle. The fruits mean weight, yield and days from planting to harvest with the use of 2,4-D were superior to natural pollination. Increasing the dose of 2,4-D resulted in an increase in yield and fruit mean weight until to dose 250 mg L-1. There was a reduction in the cycle culture with increasing in the 2,4-D doses.